Contextualizing Senior Executive Advice Seeking: The Role of Decision Process Comprehensiveness and Empowerment Climate. Issue 4 (April 2020) - Alexiev, Alexander; Volberda, Henk; Jansen, Justin; Van Den Bosch, Frans
Senior executives can seek advice both inside and outside the boundaries of the organization and that can affect the choices made and the overall direction of the organization. Perceived environmental dynamism is a primary antecedent of this behaviour as it substantially increases the information-processing demands when solving strategic decision problems. We drew on two 'fit' perspectives to theorize about the organizational contingencies of this relationship. First, fit as mediation develops when executive advice seeking takes place after a comprehensive decision process has been used in response to an increase in perceived environmental dynamism. Decision process comprehensiveness fully mediates the relationship between perceived environmental dynamism and internal advice seeking and partially mediates the relationship between perceived environmental dynamism and external advice seeking. Second, fit as moderation develops when empowerment climate weakens this indirect relationship. Decision process comprehensiveness and empowerment climate function as Edgeworth–Pareto substitutes showing that, with regard to senior executive advice seeking, there is negative synergy between decision process comprehensiveness and empowerment climate. The results of our study support the notion that there is a link between information processing at the individual and organizational level, and, more importantly, suggest that power sharing within organizations can reduce the need for senior executive advice seeking when there is decision process comprehensiveness. By elaborating the information-processing perspective on advice seeking and introducing theory on organizational structural power interdependencies, we take the first steps towards a more contextualized and realistic understanding of this phenomenon.